Effectivenessandtolerabilityofliraglutideforthemanagementofweightregainfollowingsleevegastrectomy - Jamal, Mohammad; Qasem, Wafa; Hamshari, Fatima; Dsouza, Carol; Alqallaf, Nagi; Otiku, Paul; Nnaji, Chukwudi A (John Wiley & Sons, Ltd, 2024)
Abstract Background There is currently very little research evidence on the benefits and safety of liraglutide in the management of weight regain or inadequate weight loss following metabolic and bariatric surgery. This study aimed to determine the clinical effectiveness and tolerability of liraglutide as an adjunct therapy for managing weight regain and inadequate weight loss following sleeve gastrectomy (SG).Methods This was a retrospective analysis of medical records conducted at a private clinic in Kuwait.ResultsData of 57 post-SG patients were included in the analysis. The mean (±SD) pre-treatment weight was 96.12 (29.26) kg. Following a median liraglutide treatment duration of approximately 3 months, the mean post-treatment weight was 90.19 (26.82) kg. This represents a statistically significant mean weight loss of 5.94 (6.31) kg (p < 0.001), corresponding to a loss of 6.20% of pre-treatment weight. Patients aged 31-40 years achieved a greater post-treatment weight loss of 7.63 (7.41) kg, a loss of 7.80%, relative to age groups after treatment (p = 0.047). Patients who tolerated ≥2.4 mg of liraglutide recorded a higher mean weight loss of 8.42 (7.63) kg, a loss of 8.10% (p = 0.010).Conclusion The use of liraglutide may be an effective adjunct treatment for weight optimization following SG. Maximizing the tolerable dose may yield greater weight reduction.
Keywords: bariatric surgery, liraglutide, obesity, sleeve‐gastrectomy, weight management